Conceptual Study Of Central Government Policies In Resolving The Papua Conflict In Indonesia (Papua Special Autonomy Perspective) - Methodius KOSSAY (Indonesia Strategic Sustainability, 2022)
Since the implementation of Special Autonomy in Papua, various policies have been implemented by the central government to resolve conflicts in Papua. This policy is carried out through several regulations regarding the acceleration of welfare development in Papua as a way to resolve the Papuan conflict. The method used in this paper is juridical-normative with a conceptual approach to researching library materials using the object of the study of writing in the form of existing libraries. The purpose of this paper is to find out the policies of the Central Government in resolving the Papuan Conflict in Indonesia (Papua Special Autonomy Perspective). With the results of his research that the Central Government's policy in resolving the Papuan conflict in Indonesia (Papua Special Autonomy Perspective) is to solve the root problems in Papua with a welfare and security development policy under the legal umbrella of the Papua Special Autonomy Law and its derivatives regulations. However, this policy has not had a significant impact on resolving the conflict in Papua because it has not resolved the roots of the conflict that occurred in Papua. So one of the steps that must be taken is to open a space for peaceful dialogue to resolve the conflict thoroughly, thoroughly and with dignity.